Strategi Pengembangan Program Desa Mandiri Untuk Cegah Stunting Melalui Pemberian Makanan Tambahan Balita di Desa Jambangan Kecamatan Candi - fara adiba adiba; Isna Fitria Agustina (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Stunting remains a serious issue in many villages in Indonesia, including Jambangan Village in Candi District, requiring effective prevention strategies. This study aims to analyze and describe strategies for developing independent village programs to prevent stunting through the provision of supplementary food for toddlers in Jambangan Village. The study used qualitative methods with purposive sampling techniques to select relevant informants based on their roles and involvement in the program. The results were analyzed using Kotten's government strategy theory with three indicators. First, the organizational strategy showed that stunting prevention efforts were in line with the village's strategic objectives through the Healthy Village House program and stunting discussions involving various stakeholders. Second, the resource support strategy showed the utilization of local assets in the form of human resources, food, and village funds to support the PMT program with the active role of posyandu cadres, health workers, and village officials. Third, the PMT program strategy had a positive impact on the effectiveness and sustainability of stunting reduction, although it was still constrained by low public awareness of nutrition, budget limitations, and the number of posyandu cadres.